Dynamic Analysis and Optimization of the Planar Model of the Trolleybus Škoda 21Tr - Segľa, Stefan; Kampo, Jan; Soukup, Josef (Manufacturing Technology Journal, 2019)
The article deals about modelling, dynamic analysis and optimization of stiffness and damping parameters of the main suspension of the Škoda 21Tr trolleybus. The trolleybus is excited by a ride on a rough road modelled using the Shinozuka method with the specified spectral power density. After examining the impact of tire stiffness and damping on the effective values of driving comfort characteristics, dynamic tire-to-road forces, and relative displacements between sprung and unsprang mass, the effect of spring stiffness and damping of dampers in main suspension are investigated. After selecting appropriate optimization parameters, the stiffness and damping parameters of the main suspension are optimized using the MATLAB Optimization Toolbox. The objective function is the sum of the effective values of the suspension mass acceleration and its angular acceleration. The results are the improved driving comfort without increasing the dynamic forces between the tires and the road and the relative displacements between the sprung and unsprung masses.
Keywords: Road; Modelling; Vehicle dynamics; Optimization; Stochastic excitation